Effects of External lce Massage on Salivary Flow Rate - KIGUCHI, Ran; MATSUDA, Shio; OHNO, Tomohisa; FUJISHIMA, Ichiro (The Japanese Journal of Dysphagia Rehabilitation, 2007)
【Purpose】The purpose of this study was to measure the short-term and long-term effects of external ice massage on salivary secretion in healthy adults.【Subjects】All subjects were healthy volunteer adults with no history of dysphagia and were not taking medications known to affect salivary flow. Short-term study：36 healthy adults (14 males, 22 females, average age：mean±SD＝29.2 ± 6.5 years). Long-term study：Ice massage group：22 healthy adults (11 males, 11 females, average age：30.4 ± 5.8 years). Control group：15 healthy adults (2 males, 13 females, average age：26.9 ± 5.0 years).【Methods】Unstimulated whole saliva (UWS) was collected by spitting. Saliva collections were made at almost the same time in the late afternoon to reduce the influence of circadian rhythm on salivary flow rate. UWS samples were weighed every five minutes for 30 minutes and the salivary fiow rate (SFR ml/min) was calculated. Short-term study：Each subject performed two different saliva collections on two separate days. With ice massage：After 30 minutes of saliva collection, each subject ice-massaged the skin overlying the salivary glands with an ice-filled container for 10 minutes followed by 30 minutes of saliva collection. No ice massage：After 30 minutes of saliva collection, the subject rested for 10-minutes followed by 30 minutes of saliva collection. Long-term study：Ice massage group：Saliva was collected for 30 minutes at least one day before the first ice massage session. Each subject performed three separate 10-minute sessions of ice massage daily for seven days. On the seventh and final day, saliva was collected for 30 minutes without the last session of ice massage. Control group：Saliva was collected for 30 minutes. After seven or eight days, saliva was collected for 30 minutes.【Results】Short-term study：The paired t-test showed a significant reduction in salivary flow immediately after ice massage (p ＝ 0.002). Long-term study：The paired t-test showed a significant reduction in salivary flow after seven days of ice massage three times a day (p ＝ 0.033).【Conclusion】 We performed two studies to measure the short-term and long-term effects of ice massage applied to the skin overlying the salivary glands on salivary flow rate. The results suggest that the ice massage reduces salivary flow after a single session of application, and after multiple applications over several sessions. A more thorough study with appropriate controls and a study on patients with sialorrhea should be conducted.